Peningkatan Ketahanan Pangan Melalui Penguatan Kelompok Tani - Barokatuminalloh Barokatuminalloh; Neni Widayaningsih; Diah Setyorini Gunawan (Universitas Muhammadiyah Ponorogo, 2018)
The research is based on the low household food security in Banyumas regency. One way to improve it is by empowering farmer groups. The growing group of farmers is